ANALISIS BERPIKIR KRITIS SISWA YANG BERGAYA KOGNITIF REFLEKTIF DAN IMPULSIF PADA PEMBELAJARAN BIOLOGI MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MEDIA GAMBAR - Ulfa Muryani; Imas Cintamulya (Program Studi Pendidikan Biologi, 2018)
ABSTRACT Teaching done by teachers during this time to give more lectures and exercises to do the problems quickly without understanding the concept in depth. This causes poorly trained students to develop their reasoning power. In order for meaningful knowledge to occur, teachers must train students to think critically which is necessary at this point. In addition, another aspect that must be considered a teacher is the cognitive style of students, because each student has a different cognitive style. For that reason, it is necessary to do research on cognitive and impulsive cognitive-style student analysis on biology learning through problem based learning model with image media with the aim to describe students' critical thinking ability with reflective and impulsive cognitive style. The subjects in this study as many as 25 students of class VII F SMP Negeri 1 Sluke consisting of 8 students who reflective cognitive style and 8 students of cognitive impulsive style. Technique of collecting data in the form of Matching Familiar Test Test developed by Warli to know the cognitive style of student, while critical thinking data of student use student's critical thinking ability test which refer to Ennis indicator. Critical thinking data of reflective and impulsive cognitive students were then tested using nonparametric statistics with Mann Whitney test. The results showed that there is a difference between students who reflective and impulsive cognitive style in which the student's reflective cognitive style is higher than the student's cognitive impulse score. Thus it can be concluded that students' critical thinking skills are reflective cognitive style better than the critical thinking skills of cognitive impulsive students on biology learning using Problem Based Learning model with image media.Keywords: critical thinking, Reflective cognitive style, Impulsive cognitive style, Problem based learning, media images.